2009
DOI: 10.3844/ajeassp.2009.759.763
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of Residual Stress Part 2: Relaxation of Stage 2

Abstract: Problem statement: Compressive residual stress induced by surface treatment such as shot peening increased component’s fatigue life. However the initial induced residual stresses relax during component operating life and it is important to consider the relaxation in the design. Approach: In this study, a 2024-T351 aluminum alloy specimens were shot peened into three shot peening intensities condition to induce compressive residual stresses. Then fatigue test for two loads was performed for the 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Hence, residual stresses can be beneficial or harmful as long as they are stable. However, due to cyclic loading, the relaxation of such stresses is a well-known phenomenon [4][5][6][7][8]. It has been found that this relaxation depends on the initial residual stress, the actual material, and the loading condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, residual stresses can be beneficial or harmful as long as they are stable. However, due to cyclic loading, the relaxation of such stresses is a well-known phenomenon [4][5][6][7][8]. It has been found that this relaxation depends on the initial residual stress, the actual material, and the loading condition.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that this relaxation depends on the initial residual stress, the actual material, and the loading condition. It has been showed that the amount of residual stress relaxation is very low [6], [7], [8] in the case where the applied cyclic loading does not cause micro-plasticity. While the higher amount of residual stress relaxation noted with load cycles cause macro-plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…2 supports the linear logarithmic decreasing relationship between residual stress and loading cycle only after the first cycle. However, relaxation of the compressive residual stress in the first cycle reached more than 40% [5,6]. Kodama model does not considered this large amount of first cycle relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of the residual stress relaxation models can be found in [7]. The relaxation of residual stress in the first stage (surface yielding) and the second stage (subsequent cycles) for 2024-T351 were investigated [8,9], the result showed that the compressive residual stress relaxation is found to be more than 50% of its initial state of stress.…”
Section: Introductionmentioning
confidence: 99%